Exploration of Antigen Induced CaCO3 Nanoparticles for Therapeutic Vaccine. Issue 14 (22nd February 2018) - Wang, Shuang; Ni, Dezhi; Yue, Hua; Luo, Nana; Xi, Xiaobo; Wang, Yugang; Shi, Min; Wei, Wei; Ma, Guanghui
Abstract: Therapeutic vaccines possess particular advantages and show promising potential to combat burdening diseases, such as acquired immunodeficiency syndrome, hepatitis, and even cancers. An efficient therapeutic vaccine would strengthen the immune system and eventually eliminate target cells through cytotoxic T lymphocytes (CTLs). Unfortunately, insufficient efficacy in triggering such an adaptive immune response is a problem that remains unsolved. To achieve efficient cellular immunity, antigen‐presenting cells must capture and further cross‐present disease‐associated antigens to CD8 T cells via major histocompatibility complex I molecules. Here, a biomimetic strategy is developed to fabricate hierarchical ovalbumin@CaCO3 nanoparticles (OVA@NP, ≈500 nm) under the templating effect of antigen OVA. Taking advantage of the unique physicochemical properties of crystalline vaterite, cluster structure, and high loading, OVA@NP can efficiently ferry cargo antigen to dendritic cells and blast lysosomes for antigen escape to the cytoplasm. In addition, the first evidence that the physical stress from generated CO2 induces autophagy through the LC3/Beclin 1 pathways is presented. These outcomes cooperatively promote antigen cross‐presentation, elicit CD8 T cell proliferation, ignite a potent and specific CTL response, and finally achieve prominent tumor therapy effects. Abstract : Biomimetically prepared ovalbumin@CaCO3 nanoparticles are demonstrated to efficiently ferry cargo antigen to dendritic cells and blast lysosomes for antigen escape to cytoplasm. Meanwhile, the mechanical stress sourced from generated CO2 also induces autophagy. These outcomes cooperate to promote the antigen cross‐presentation, elicit CD8 T cell proliferation, ignite a potent and specific cytotoxic T lymphocyte response, and finally achieve prominent tumor therapy effects.